Website para a promoção da adesão ao tratamento antirretroviral de adultos que vivem com HIV: avaliação pelo público-alvo - Machado, Aiodêlle dos Santos (2024)
Introduction: it is estimated that by the end of 2022, about 37,5 million of adults lived with the Human Immunodeficiency Virus in the world, and about 29,8 million of people had access to antiretroviral therapy in the same period. Understanding the access to medication is not determinant for treatment adherence, World Health Organization recommends the utilization of non-pharmacological interventions to adherence promotion. This strategy must consider the situational reality of the place in which there is the intention to implement it and the target public that will be accessed. Aim: to evaluate an educational-caring technology of the type website, to promote antiretroviral treatment adherence to the Human Immunodeficiency Virus by the adult target audience. Method: methodological study, developed through the Conceptual and Theoretical Framework Knowledge to Action Translation, contemplating the step of creating of a website and evaluation with the target audience. The creation stel was developed in partnership between the Research Group Caring to People, Families and Society's Health and the Tutorial Education Program - Computer Science, both from the Federal University of Santa Maria. For the evaluation by the target audience step, collective and individual interviews were developed in the Specialized Assistance Service/Sexually Transmitted Infection Testing and Counselling Center, using a sociodemographic data collection questionnaire and the Assistive Technology Assessment Tool to evaluate the website attributes. Interviews were developed between July and September 2023 and counted with the participation of eight adults that live with the Human Immunodeficiency Virus. Results: in the creation phase, there was an website to antiretroviral treatment adherence promotion of adults that live with the Human Immunodeficiency Virus. In the evaluation stage by the target audience, information was included, and adjustments were made to the layout initially presented, such as, for example, making the titles more discreet and changing colors. About the evaluation by the used tool, the website reached a mean of 1,88, being considered adequate to the target audience. Final considerations: the website may be used by adults that live with the Human Immunodeficiency Virus. As contributions in the assistance or care sphere, the easiness to navigate through information in the website was cited, for it is a tool in the digital format with free access. Beyond that, the incorporation of safe and reliable information in available tools for the population and health professionals contribute in the health education field.